CHARACTERISTICS OF THE REGIONAL SOCIO-ECONOMIC DEVELOPMENT OF THE SOUTHERN FEDERAL DISTRICT - Elmira A. Ashhotova; Violetta V. Rokotyanskaya (Статистика и экономика)
The article discusses the theoretical foundations of the «region» concept. On the basis of statistical analysis, socio-economic and reproductive tendencies of development of the SFD regions are determined, what brought to lite priority directions of modernization of the regional economy.